AN ANALYSIS OF ENGLISH DEIXIS IN SELECTED POETRY BY ERNEST HEMINGWAY - Atika Yuni Sahputri; Eni Rosnija; Eka Fajar Rahmani (LPPM Universitas PGRI Jombang, 2024)
The purpose of this study is to identify the types deixis and the dominant deixis used in selected poem by Ernest Hemingway. This study was conducted through qualitative descriptive and analyzed by using the method by Milles and Huberman emphasizes a systematic process to analysis the data. The data were analyzed based on Levinson’s theory of the types of deixis. The data from selected poems by Ernest Hemingway such as Along with Youth, The Age Demanded, Advice to A Son, and I Like American. The findings indicate that the types of deixis found in selected poem by Ernest Hemingway are the person deixis, time deixis, place deixis and discourse deixis. From the analyzed got 48 data and the result of this research show that person deixis is used 39 times (81%), time deixis only used one time (2%), place deixis is used 2 times (13%), discourse deixis is used 6 times (13%). The most dominant types of deixis used in selected poems is person deixis, and most used in I Like American poem 27 times.